A Potential Late Stage Intermediate of Twin-Arginine Dependent Protein Translocation in Escherichia coli - Geise, Hendrik; Heidrich, Eyleen Sabine; Nikolin, Christoph Stefan; Mehner-Breitfeld, Denise; Brüser, Thomas (Frontiers in Microbiology, 2019)
The twin-arginine translocation (Tat) system transports folded proteins across membranes of prokaryotes, plant plastids, and some mitochondria. According to blue-native polyacrylamide gel electrophoresis, distinct interactions between the components TatA, TatB, and TatC result in two major Tat complexes in Escherichia coli that can bind protein substrates. We now report the first detection of a TatABC complex that likely represents the state at which transport occurs. This complex was initially found when the photo cross-linking amino acid p-benzoyl-L-phenylalanine (Bpa) was introduced at position I50 on the periplasmic side of the first trans-membrane domain of TatC. Cross-linking of TatCI50Bpa resulted in TatC-TatC-cross-links, indicating a close proximity to neighboring TatC in the complex. However, the shift was not caused by cross-links but rather by non-covalent side chain interactions, as it was also detectable without UV-cross-linking or with an I50Y exchange. The new complex did not contain any detectable substrate. It was slightly upshifted relative to previously reported substrate-containing TatABC complexes. In the absence of TatA, an inactive TatBCI50Bpa complex was formed of the size of wild type substrate-containing TatABC complexes, suggesting that TatB occupies TatA binding sites at TatCI50Bpa. When substrate binding was abolished by point mutations, this TatBCI50Bpa complex shifted analogously to active TatABCI50Bpa complexes, indicating that a defect substrate binding site further enhances TatB association to TatA binding sites. Only TatA could shift the complex with an intact substrate binding site, which explains the TatA-requirement for substrate transport by TatABC systems.